Influence de l’extrait hydroéthanolique de Laurus nobilis L., sur la qualité de la viande de poulet de chair conservée à 4°C. - KADDOUR, Hind; MOUSSA, Yamna (My University, 2021)
This s tudy aims to follow the antimicrobial effect of the hydroethanoli c extract of LaurusnobilisL., (Laurie r) on the microbiological quality of broiler meat during cold s torage. The lea ves of Laurusnobilis (Laurel) were collected in the region of Mos taganem. The extraction was carried out by maceration of a ground mixture of dried bay lea ves for 6 hours in an aqueous e thanol solution. The hydroethanoli c extract obtained after filtration and e vaporation was added in tripli cate a t a rate of 0, 1 and 2% on 300g pieces of broiler pectoral meat, ea ch distributed in a polys tyrene tray. Mea ts, whether or not trea ted with bay leaf extract, were then s tored at 4 ° C for 9 days. The microbiological analyzes carrie d out on the experimental samples during s torage concerned the enumeration of : total ge rms , fecal coliforms , Staphylococcus aureus and pseudomonas. The resul ts were subjected to a randomized a nalysis of variance and a comparison of means two by two according to the tes t of Newman and Keuls. Before the 3rd day of s torage a t 4 ° C, the microbiological quality of the broiler meat enriched with hydroethanoli c extract of Laurusnobilus L. a t 2% as a natural additive was clea rly prese rved. However, the duration of cold s torage of chicken pectoral mea t cannot exceed 3 da ys of s torage during and beyond whi ch a s trong contamination with Staphylococcus aureus and Pseudomonas seems to be decla red.
Keywords: Laurusnobilis L; meat; broiler; cold; quality; microbiology